Legal Analysis on Regulations of London Convention 1972 And Its Protocol: Implementation and Participation in Countries - Asif Khan; Nazar Hussain; Dr. Liaquat Ali Chandio; Sahib Oad (Journal of Peace, Development and Communication, 2023)
To prohibit marine pollution from ship waste and other materials being dumped into the ocean, the London Convention of 1972 as well as its Protocol were created. This article examines the rules of the London Convention and also its Protocol on the dumping of hazardous materials and other substances and provides historical context for the two ocean dumping treaties. The article then contrasts how the London Convention of 1972 and its Protocol were ratified and implemented in various nations, concentrating on P.R.China, the United States, and commonwealth of Australia. In-depth information is provided on the application of the London Convention and also its Protocol in China, including general rules, designating specific areas of water for waste disposal, fees and authorizations, and dumping rules. The article also covers the London Convention’s implementation in the United States, such as rules governing research, monitoring coastal water quality, and ocean dumping. Australia’s compliance with the London Convention and also its Protocol is also investigated. Generally speaking, this article examines the differing degrees of engagement and application of these regulations in various nations while highlighting the significance of the London Convention of 1972 and its Protocol throughout preventing marine pollution.